Hutchinson-Gilford Progeria Syndrome (HGPS) - relevant aspects of a rare syndrome diagnosed in a Brazilian child - Nogueira, Alexandre Simoes; Nogueira, Carlos Bruno Pinheiro; Medeiros, Rômulo; Beviláqua, Ana Cristina; Santos, Paulo Sérgio da Silva; Rubira-Bullen, Izabel Regina Fischer; Gonçales, Eduardo Sanches (Journal of Oral Diagnosis, 2016)
Hutchinson-Gilford Progeria Syndrome (HGPS) is an extremely rare genetic condition characterized by premature aging and it’s about one case for every four to eight million people. Children affected usually have premature death due to cardiovascular problems. The gene that causes progeria was recently discovered and it has attracted the interest of the scientific community worldwide not only by the possibility of cure of this genetic pathology but also because of the possibility to retard or to minimize the effects of premature aging caused by the disease in human beings. Among the oral and facial findings is remarkable the delay in tooth eruption, the micrognathia and the disproportion between the skull and face. Dental treatment is directed to preventive aspects and strict supervision of oral conditions in order to minimize the need for more invasive treatments. The authors highlight the most relevant aspects related to that syndrome, emphasizing the important aspects to all the oral and maxillofacial surgeons, reporting a case of progeria in a five-year old Brazilian child.